Right to a Fair Trial - Frumarová, Kateřina (The European Convention on Human Rights: A Central and Eastern European Perspective, 2026)
The chapter focuses on one of the fundamental rights enshrined in the Convention, the right to a fair trial. Attention is paid both to clarifying the nature of this right and to the basic concepts underlying its application, which must be interpreted in an autonomous manner. The individual rights which, in their totality, constitute and fulfil the right to a fair trial as a concept inseparable from any democratic state governed by the rule of law, are analysed in detail. Interpreting this right requires in particular a close examination of the ECtHR’s broad case law, which concretises and illuminates the right in its sub-aspects and levels.Keywords: right to a fair trial, civil rights and obligations, criminal charges, fair and public proceedings, reasonable time, Article 6 of the Convention, European Court of Human Rights